ANALYSIS OF FACTORS INFLUENCING LOYALTY THROUGH SATISFACTION AND TRUST ON BNI MOBILE BANKING USERS IN SAMARINDA CITY, EAST KALIMANTAN - Armini Ningsih; Suminto; Feti Fahmimroah; Tito Adiyatma Dwiyanto (CV. RADJA PUBLIKA, 2024)
The purpose of this study were to analyze and prove the effect of electronic service quality, perceived risk, information quality, on loyalty through satisfaction and trust in BNI Mobile Banking users in Samarinda City. This study used a questionnaire with a sample of 160 BNI Mobile Banking users in the city. This research used a quantitative approach with path analysis which was processed with IBM SPSS Statistic 23.0 software and Structural Equation Modeling (SEM) with AMOS 5.0 software. Accidental random sampling was employed in this study, with a measurement scale using a Likert scale with a score of 1 to 5. The test instrument was validity and reliability test and the classical assumption tests such as linearity test, normality test, multicollinearity test were used. Then the estimation test and structural model fit test were carried out. Based on the structural model, it could be proven that there was a significant influence between the variables electronic service quality and Information Quality on Satisfaction; Electronic Service Quality, Information Quality, and satisfaction on trust; trust on loyalty for BNI Mobile Banking users in Samarinda City. Meanwhile, there was an insignificant influence between the variables perceived risk on satisfaction; perceived risk on trust; electronic service quality and satisfaction on Loyalty.